A Blooming Island Beneath the Patrilineal Canopy: Balinese Women and the Politics of Reproduction - Sukardiasih, Ni Luh Gede; Ratih Swandewi , Luh Kadek; Septya Titisari , Anastasia; Kistiana , Sari; Chetri, Alka (Universitas Udayana, 2025)
The family planning (KB) Krama Bali policy aims to counter Bali’s fertility decline and rising in-migration by promoting a four-child ideal to sustain the indigenous population. However, this policy challenges Balinese women’s reproductive rights and family preferences. Through in-depth interviews with 34 married Balinese women conducted in 2020 and 2022, this study explores how KB Krama Bali shapes fertility decisions, family size preferences, and gender expectations. Findings reveal three key themes: the number of children women prefer, their perception of an ideal family size, and their desire to have a son. Balinese women navigate conflicting pressures from local family planning policies, economic burdens, and the patrilineal system. Their triple role in economic contributions, reproductive function, and adat (customs) obligations underscores their role in preserving Balinese identity. This study highlights the need for gender-sensitive policies that balance demographic goals with women’s autonomy and well-being